1989
DOI: 10.1119/1.15864
|View full text |Cite
|
Sign up to set email alerts
|

Baseball–bat collisions and the resulting trajectories of spinning balls

Abstract: The collision between a baseball and a bat has been analyzed using the classical theory of rigid body collisions. Also computed are the ranges of batted balls for a variety of launch angles and rotation rates, accounting for both drag and lift forces. If the coefficient of friction is not too small, the batter can give the ball fairly large backspin without fouling it off by swinging under the ball by as much as 1 to 2.5 cm. The increased range resulting from backspin is large, of the order of several tens of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 0 publications
1
14
0
Order By: Relevance
“…These data are roughly consistent with C L = S, independent of Re, which is the parametrization used by Watts and Baroni. 4,6 The data of Alaways 8,9 were obtained using a high-speed motion analysis technique to measure the spin vector and track the trajectory of a pitched baseball. From these data C L was extracted for S in the range S = 0.1-0.5 and for speeds up to approximately 75 mph.…”
Section: Previous Determinations Of the Magnus Forcementioning
confidence: 99%
See 1 more Smart Citation
“…These data are roughly consistent with C L = S, independent of Re, which is the parametrization used by Watts and Baroni. 4,6 The data of Alaways 8,9 were obtained using a high-speed motion analysis technique to measure the spin vector and track the trajectory of a pitched baseball. From these data C L was extracted for S in the range S = 0.1-0.5 and for speeds up to approximately 75 mph.…”
Section: Previous Determinations Of the Magnus Forcementioning
confidence: 99%
“…Computational studies of the effect of spin on the flight of hit baseballs have been reported by Rex, 3 Watts and Baroni, 4 and Sawicki et al 5 These studies utilized models of the Magnus force based on the available experimental information, which will be reviewed in Sec. II.…”
Section: Introductionmentioning
confidence: 99%
“…7 Typically, complications only arise when the ball impacts either at an oblique angle or if the object impacts while spinning. Many experimental and theoretical studies [7][8][9][10][11][12][13] have been performed over the years to investigate the interactions between an impacting object and the surface of a material. The authors have been developing a material where common knowledge does not apply because non-spinning objects …”
Section: Embedding Simple Machines To Add Novel Dynamic Functions To mentioning
confidence: 99%
“…16 for spindown with little or no translational velocity was used in Ref. 17 as justification for neglecting spin-down entirely. These results 16 predict a baseball spin-down characteristic time of about 250 s. It is difficult to determine if the spin-down rate will increase or decrease when a large translational velocity is added.…”
Section: Spin-downmentioning
confidence: 99%